Integrating Extremely Low Frequency Magnetic Field Studies in Science Education: “A Case Study on 500 kV Extra High Voltage Transmission Lines" - Rista Setiani; Sudarti Sudarti; Sumardi Sumardi; Singgih Bektiarso; Wahyu Muldayani; Dina Helianti; Ayu Munawaroh Aziz; Aditya Kurniawan; Rio Dermawan; Tania Ardiani (Jurnal Penelitian Pendidikan IPA, 2025)
Introduction: Until now, the impact of Extremely Low Frequency electromagnetic field radiation (ELF-EMF) by extra high voltage transmission lines (500 kV-EHVTL) is still debated. While WHO recommends a threshold of magnetic field exposure of 100 µT for up to 24 hours/day is declared safe for health. This study aims to examine the Integration of Extremely Low Frequency Magnetic Field Studies in Science Education: "Case Study on 500 kV-EHVTL". This study is important to support literacy in Environmental Physics and Environmental Radiation courses. The location of the study is a 500 kV EHVTL building located in Gondang Wetan District, Pasuruan Regency, East Java, Indonesia. Measurement of ELF magnetic field intensity using the EMF Tester-827 tool. The measurement position is at point 0 (directly below), and lateral distances of 50m, 100m, 150m, 200m, and 250m from the EHVTL power grid cable, as well as distances of 0m, 1m, 5m, 10m, and 15m from the EHVTL power grid tower. The intensity of ELF magnetic field exposure just below the EHVTL reached a value of 5.73 µT-10,085 µT (increased 170-234 times) compared to the natural magnetic field. While several research results prove that exposure to magnetic fields with an intensity of around 10 µT in vitro causes an increase in cell proliferation. Increased cell proliferation in the human body can have negative effects on health. Based on the research results it was concluded that an increase in the intensity of ELF magnetic field exposure up to 170-234 times can cause biological effects at the cellular level and has the potential to cause health impacts on humans. it is advisable to avoid living under the EHVTL network, and the WHO recommendation that the threshold exposure value of 100 µT is declared safe for humans exposed for up to 24 hours/day needs to be reviewed